Tuberculosis drug discovery in the post‐post‐genomic era. Issue 2 (8th January 2014) - Lechartier, Benoit; Rybniker, Jan; Zumla, Alimuddin; Cole, Stewart T
Abstract The expectation that genomics would result in new therapeutic interventions for infectious diseases remains unfulfilled. In the post‐genomic era, the decade immediately following the availability of the genome sequence of Mycobacterium tuberculosis, tuberculosis (TB) drug discovery relied heavily on the target‐based approach but this proved unsuccessful leading to a return to whole cell screening. Genomics underpinned screening by providing knowledge and many enabling technologies, most importantly whole genome resequencing to find resistance mutations and targets, and this resulted in a selection of leads and new TB drug candidates that are reviewed here. Unexpectedly, many new targets were found to be 'promiscuous' as they were inhibited by a variety of different compounds. In the post‐post‐genomics era, more advanced technologies have been implemented and these include high‐content screening, screening for inhibitors of latency, the use of conditional knock‐down mutants for validated targets and siRNA screens. In addition, immunomodulation and pharmacological manipulation of host functions are being explored in an attempt to widen our therapeutic options.